Prevalence of depressive disorders in adolescents - Richter, Paul; Alvarado, Luis; Fend, Helmut (Revista de Psicología, 1997)
Research about prevalence of depressive disorders in adolescence are rare. Data concerning the true prevalence of depression in adolescents are still missing. As part of a very large follow-up research about development in adolescence, the prevalence of depression in young males and females assessed by means the Beck Depression Inventory (BDI), a world-widely used screening tool for the assessment of depression. Our data shows that about 20% of young males and females (sex differences were quite irrelevant) were suffering from moderate to severe depressive symptoms. Moreover, 22% of them were severely worried with suicide thoughts. Results are discussed on the background of current research in this area. Differences between clinical and psychometrical assessment of depressive disorders are also pointed out.